The frequency of EGFR and KRAS mutations in non-small cell lung cancer (NSCLC): routine screening data for central Europe from a cohort study. Issue 4 (3rd April 2013) - Boch, Christian; Kollmeier, Jens; Roth, Andreas; Stephan-Falkenau, Susann; Misch, Daniel; Grüning, Wolfram; Bauer, Torsten Thomas; Mairinger, Thomas
Abstract : Objectives: Owing to novel therapy strategies in epidermal growth factor receptor (EGFR)-mutated patients, molecular analysis of the EGFR and KRAS genome has become crucial for routine diagnostics. Till date these data have been derived mostly from clinical trials, and thus collected in pre-selected populations. We therefore screened 'allcomers' with a newly diagnosed non-small cell lung carcinoma (NSCLC) for the frequencies of these mutations. Design: A cohort study. Setting: Lung cancer centre in a tertiary care hospital. Participants: Within 15 months, a total of 552 cases with NSCLC were eligible for analysis. Primary and secondary outcome measures: Frequency of scrutinising exons 18, 19 and 21 for the presence of activating EGFR mutation and secondary codon 12 and 13 for activating KRAS mutations. Results: Of the 552 patients, 27 (4.9%) showed a mutation of EGFR. 19 of these patients (70%) had deletion E746-A750 in codon 19 or deletion L858R in codon 21. Adenocarcinoma (ACA) was the most frequent histology among patients with EGFR mutations (ACA, 22/254 (8.7%) vs non-ACA, 5/298 (1.7%); p<0.001). Regarding only ACA, the percentage of EGFR mutations was higher in women (16/116 (14%) women vs 6/138 (4.3%) men; p=0.008). Tumours with an activating EGFR mutation were more likely to be from non-smokers (18/27; 67%) rather than smoker (9/27; 33%). KRAS mutation was present in 85 (15%) of all cases. In 73 patients (86%), the mutation was found in exon 12 and in 12 cases (14%) in exon 13. Similarly, ACA had a higher frequency of KRAS mutations than non-ACA (67/254 (26%) vs 18/298 (6.0%); p<0.001). Conclusions: We found a lower frequency for EGFR and KRAS mutations in an unselected Caucasian patient cohort as previously published. Taking our results into account, clinical trials may overestimate the mutation frequency for EGFR and KRAS in NSCLC due to important selection biases.